Discovering the City: Crowdsourcing and Personalized Urban Paths Across Cultural Heritage - Delnevo, Giovanni; Melis, Andrea; Mirri, Silvia; Monti, Lorenzo; Prandini, Marco (Smart Objects and Technologies for Social Good, 2018)
Travel planners and mobile applications related to cultural heritage can play an interesting role in the development of smart cities, when they are integrated each other, engaging the user in touristic and entertainment activities, letting him/her be a source of cultural resources. This paper focuses on a microservices-based architecture, defined with the aim of providing support in computing personalized urban paths across cultural heritage places and in sharing multimedia resources about points of interest. A prototype of mobile application has been implemented on the basis of such architecture, showing the feasibility of the proposed approach thanks to personas and related scenarios.